2020
DOI: 10.1002/bjs.11703
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open colorectal surgery in the acute setting (LaCeS trial): a multicentre randomized feasibility trial

Abstract: Background: Approximately 30 000 people undergo major emergency abdominal gastrointestinal surgery annually, and 36 per cent of these procedures (around 10 800) are carried out for emergency colorectal pathology. Some 14 per cent of all patients requiring emergency surgery have a laparoscopic procedure. The aims of the LaCeS (laparoscopic versus open colorectal surgery in the acute setting) feasibility trial were to assess the feasibility, safety and acceptability of performing a large-scale definitive phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
(37 reference statements)
0
25
0
1
Order By: Relevance
“…The recent LaCeS trial has demonstrated that randomization of a cohort of ES patients between laparoscopic and an open surgical approach is feasible, acceptable and safe, albeit with a conversion rate of 39% [ 271 ]. Vallance et al [ 272 ] have examined patient and institutional factors associated with the laparoscopic approach for urgent surgery for colorectal cancer in the English National Bowel Cancer Audit.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The recent LaCeS trial has demonstrated that randomization of a cohort of ES patients between laparoscopic and an open surgical approach is feasible, acceptable and safe, albeit with a conversion rate of 39% [ 271 ]. Vallance et al [ 272 ] have examined patient and institutional factors associated with the laparoscopic approach for urgent surgery for colorectal cancer in the English National Bowel Cancer Audit.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…However, if the evidence supports subspecialists having superior outcomes to their counterparts then an alternative model may be required. Following the recent LaCeS trial, which showed an acceptable safety profile for emergency laparoscopic colorectal surgery, we are likely to see further studies assessing this and an increasing use of laparoscopic surgery in the emergency setting [42]. To enable this, we must ensure there is an appropriately structured workforce and trained specialist care available.…”
Section: Discussionmentioning
confidence: 99%
“…showed an acceptable safety profile for emergency laparoscopic colorectal surgery, we are likely to see further studies assessing this and an increasing use of laparoscopic surgery in the emergency setting [42]. To enable this, we must ensure there is an appropriately structured workforce and trained specialist care available.…”
Section: Predictors Of 30-day Postoperative Mortality In Patients Undmentioning
confidence: 99%
“…The 'Laparoscopic versus open colorectal surgery in the acute setting' (LaCeS) multicentre randomized feasibility trial 12 recruited from five UK NHS Trusts and randomized patients presenting with acute colorectal pathology requiring resection, to receive laparoscopic or open surgery. The trial was registered with registration number: ISRCTN15681041 (http://www.controlled-trials.com).…”
Section: Methodsmentioning
confidence: 99%